2018
DOI: 10.1089/heq.2018.0018
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities and the Effect of County Level Income on the Incidence and Survival of Young Men with Anal Cancer

Abstract: Purpose: Prior studies have identified a racial disparity in incidence and survival of squamous cell carcinoma of the anus (SCCA) in the young African American male population. We aim to determine whether racial disparities are independent of income and urban location.Methods: The National Cancer Institute's Surveillance of Epidemiology and End Results database was queried for data on patients with SCCA for the years of 2000–2013. Cox regression was used to determine the effect of race, county median family in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…Though the current study did not assess and compare incidence rates between the two groups, the racial disparities in certain demographic factors, in treatment, and in mortality between Black and White patients identified in our study draws attention to the lack of specific screening guidelines for anal SCC. Prior studies have identified young Black males as an at risk group for anal SCC, and have postulated that this may be related to changes in sexual practices over time . The current study found that Black patients with anal SCC were more likely to be younger than White patients, though it did not focus on disparities in age or sexual orientation.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Though the current study did not assess and compare incidence rates between the two groups, the racial disparities in certain demographic factors, in treatment, and in mortality between Black and White patients identified in our study draws attention to the lack of specific screening guidelines for anal SCC. Prior studies have identified young Black males as an at risk group for anal SCC, and have postulated that this may be related to changes in sexual practices over time . The current study found that Black patients with anal SCC were more likely to be younger than White patients, though it did not focus on disparities in age or sexual orientation.…”
Section: Discussionmentioning
confidence: 57%
“…There are racial disparities in cancer outcomes in the United States, with Black patients having significantly higher mortality . Prior studies have demonstrated a higher incidence of anal SCC among Black patients compared to White patients . Moreover, Black patients with anal SCC have been found to have increased mortality compared to White patients .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our point estimates are consistent with those reported in several other studies. 1,2,11,17 Conclusions These data show that although both men and women are developing anal cancer, the incidence in young adult males is climbing. Our data also suggest there are significant sociodemographic differences in anal cancer, wherein communities with a higher proportion of individuals living in poverty and a higher proportion of racial/ethnic minority groups bear the highest incidence of disease.…”
Section: Discussionmentioning
confidence: 76%
“…Receptive anal intercourse and infection with human immunodeficiency virus (HIV) are by far the most important risk factors for developing anal cancer. 9 , 10 Nelson et al, 1 and others, 11 have speculated that changes in the patterns of sexual behavior among men who have sex with men, a growing subgroup of the population in the United States, could be an important driver of the rising rates of anal cancer among men. Several previous studies have also shown a strong correlation between both cervical dysplasia and anogenital warts and the subsequent development of anal cancer.…”
Section: Discussionmentioning
confidence: 99%